2022
DOI: 10.1007/s00299-022-02831-8
|View full text |Cite
|
Sign up to set email alerts
|

Color recycling: metabolization of apocarotenoid degradation products suggests carbon regeneration via primary metabolic pathways

Abstract: Key message Analysis of carotenoid-accumulating roots revealed that oxidative carotenoid degradation yields glyoxal and methylglyoxal. Our data suggest that these compounds are detoxified via the glyoxalase system and re-enter primary metabolic pathways. Abstract Carotenoid levels in plant tissues depend on the relative rates of synthesis and degradation. We recently identified redox enzymes previously known to be involved in the detoxification of fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 80 publications
(139 reference statements)
0
5
0
1
Order By: Relevance
“…Consequently, the renewable intensity drops by half affecting the final percentage. The [TauIm]­[HSO 4 ] has the higher RP (77%) among the described examples since all reagents used to make the imidazole ring through the Debus–Radziszewski reaction, taurine, formaldehyde, and glyoxal can be obtained from renewable sources.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the renewable intensity drops by half affecting the final percentage. The [TauIm]­[HSO 4 ] has the higher RP (77%) among the described examples since all reagents used to make the imidazole ring through the Debus–Radziszewski reaction, taurine, formaldehyde, and glyoxal can be obtained from renewable sources.…”
Section: Resultsmentioning
confidence: 99%
“…graminifolia generated apocarotene-dialdehydes and produced the potential cytotoxic end product glyoxal. The increase in glyoxal under dehydration may result from lipid peroxidation and β-carotene oxidation, as mentioned by Koschmieder et al. (2022) .…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, VDE reversibly regulates these three xanthophylls. The carotenoid degradation pathway is mediated by NCED, which decomposes carotenoids to form apocarotenoids ( Koschmieder et al, 2022 ). In this study, we found that during leaf color transition, the expression levels of PSY, CRISTO, LCYE, BCH, ECH, VDE, and ZEP exhibited an upward trend, leading to a progressively increased accumulation of their respective products.…”
Section: Discussionmentioning
confidence: 99%